2017
DOI: 10.1007/s12149-017-1180-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and FDG-PET/CT findings of Epstein–Barr virus-related lymphoid neoplasms

Abstract: Epstein-Barr virus (EBV) is one of the most common viruses, infecting more than 90% of the adult population worldwide. EBV genome is detected in some lymphoid neoplasms. Not only their histopathological subtypes, but also their backgrounds and their clinical courses are variable. A number of B-cell lymphoproliferative disorders associated with the immunocompromised state are related to EBV infection. The incidences of these disorders have been increasing along with generalization of organ transplantations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Hence, the presence of extranodal hypermetabolic lesions, especially in multiple extranodal organs, was of great significance in the diagnosis of M-HLH. And it was consistent with previous studies, which suggested single extranodal organ involvement sometimes indicated NM-HLH (23,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the presence of extranodal hypermetabolic lesions, especially in multiple extranodal organs, was of great significance in the diagnosis of M-HLH. And it was consistent with previous studies, which suggested single extranodal organ involvement sometimes indicated NM-HLH (23,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 92%
“…Comparing to SUV max -LN and SUV max -LN/M, the study showed that SUV max -lesions had similar AUC and higher sensitivity and accuracy in detecting M-HLH, which indicated that the addition of the metabolic information of extranodal lesions could help finding the M-HLH better. In addition, it's reported that elder children are more likely to develop M-HLH with EBV infection (28). So age was combined with the above metabolic parameters separately in the differentiation analysis in our study.…”
Section: Discussionmentioning
confidence: 96%
“…The biopsies revealed the atypical T-lymphocyte population in predominantly intra- and paravascular position and positive EBER-in-situ-hybridization. The intravascular localization and the high glucose uptake in PET-CT is unusual [ 13 ], however immunohistochemistry staining and T-cell receptor clonality analysis providing a polyclonal population clearly ruled out aggressive lymphomas, including extranodal NK/T-cell lymphoma/leukemia, EBV-positive peripheral T-cell lymphoma or intravascular large B-cell lymphoma. The detected complex karyotype is rare, but has previously described in CAEBV related T-cell LPD [ 10 ] and might be a result of subclonal expansion of EBV-infected T-cells rather than infectious.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, it is difficult to sample tissue biopsies in the clinic; therefore, PET/CT strategies are required for selected cases. Scans investigating hypermetabolic FDG foci in the liver, spleen, and bone marrow, and also multiple FDG-avid lymph nodes and skin, are highly suggestive of EBV-associated lymphoma (14). CAEBV lesions exhibiting FDG uptake are indicative of overt lymphoma development (15).…”
Section: Caebv Diagnosticsmentioning
confidence: 99%